Success Factors of Design-Build Public Sector Projects in Malaysia - Z. P., Lee; R. A., Rahman; S. I., Doh (2019)
Various procurement methods are employed in the construction industry, with each having varying success rates. The popularity of design and build (D-B) method has been increasing worldwide because its distinctive features of integrating design and construction have successfully addressed the problems inherent in the traditional design-bid-build (D-B-B) method. Previous research efforts in Malaysia have been focused on establishing a D-B strategy, including its challenges and risks and defining a broader scope for implementing D-B in public projects. However, not many empirical studies have identified the D-B success factors in Malaysia’s construction industry. This paper aims to determine the main factors attributing to the successful application of the D-B method for public projects in Malaysia’s construction industry. Specifically, this paper answers the main research question of “What are the success factors of the D-B project delivery method in Malaysian public-sector projects?”. To achieve that objective, this study involves interviewing industry practitioners that have direct hands-on experience in managing D-B public sector projects in Malaysia. The interview data are analyzed to identify the D-B success factors in construction projects. The findings suggest that the underlying factors for successful D-B public project include client capabilities, competency of the construction leader, competency of the consultant team, organizational behavior, and effective project management system. The success factors in each underlying categories are discussed in the paper. This paper contributes a better understanding of the D-B project success factors in Malaysia’s construction industry.